Stimulated emission depletion nanoscopy reveals time-course of human immunodeficiency virus proteolytic maturation - Hanne, Janina; Göttfert, Fabian; Schimer, Jiří; Anders-Ößwein, Maria; Konvalinka, Jan; Engelhardt, Johann; Müller, Barbara; Hell, Stefan; Kräusslich, Hans-Georg (ACS nano, 2016)
Concomitant with human immunodeficiency virus type 1 (HIV-1) budding from a host cell, cleavage of the structural Gag polyproteins by the viral protease (PR) triggers complete remodeling of virion architecture. This maturation process is essential for virus infectivity. Electron tomography provided structures of immature and mature HIV-1 with a diameter of 120-140 nm, but information about the sequence and dynamics of structural rearrangements is lacking. Here, we employed super-resolution STED (stimulated emission depletion) fluorescence nanoscopy of HIV-1 carrying labeled Gag to visualize the virion architecture. The incomplete Gag lattice of immature virions was clearly distinguishable from the condensed distribution of mature protein subunits. Synchronized activation of PR within purified particles by photocleavage of a caged PR inhibitor enabled time-resolved in situ observation of the induction of proteolysis and maturation by super-resolution microscopy. This study shows the rearrangement of subviral structures in a super-resolution light microscope over time, outwitting phototoxicity and fluorophore bleaching through synchronization of a biological process by an optical switch.